2014
DOI: 10.7567/jjap.53.08lb02
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study on the formation of dipole layer at high-k/SiO2interfaces

Abstract: We show that electric dipole layer at Al 2 O 3 /SiO 2 interface is reproduced by classical molecular dynamics simulation with a simple two-body rigid ion model. The dipole layer was spontaneously formed by the migration of oxygen ions from Al 2 O 3 side to SiO 2 side. Built-in potential at the Al 2 O 3 / SiO 2 is estimated to about 0.35 V, which roughly compares with the experimental value of the flat band voltage shift. Contrary, no significant dipole layer appeared at Y 2 O 3 /SiO 2 interface. The simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The atomistic picture of the oxygen density difference accommodation model was successfully reproduced in our previous molecular dynamics (MD) simulation 18) for the Al 2 O 3 =SiO 2 system. In this simulation, there was a preferential migration of O − ions from the Al 2 O 3 side to the SiO 2 side, resulting in the formation of a built-in potential of ∼0.5 eV at the Al 2 O 3 =SiO 2 interface.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…The atomistic picture of the oxygen density difference accommodation model was successfully reproduced in our previous molecular dynamics (MD) simulation 18) for the Al 2 O 3 =SiO 2 system. In this simulation, there was a preferential migration of O − ions from the Al 2 O 3 side to the SiO 2 side, resulting in the formation of a built-in potential of ∼0.5 eV at the Al 2 O 3 =SiO 2 interface.…”
mentioning
confidence: 86%
“…In a previous study, 18,31) an imbalance of multipole potentials between the two oxide layers was proposed as the origin of the O − -ion migration. SiO 2 is composed of a covalent network of SiO 4 tetrahedra that have an octupole moment around the Si ion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the XYZ crystal can be understood as stuffing the (YZ) nzinc-blende sublattice with an X n+ ion. 22 and ScPtSb with 18 valence electrons is found to be a narrow gap semiconductor with E g = 0.7 eV. 23 The electron count is illustrated in Figure 1c.…”
Section: Half-heuslers: Crystal Structure and Electronic Structurementioning
confidence: 99%
“…From the results of the classical molecular dynamics (MD) simulation of the electrical dipole moment at the interface, it has been suggested that the negative electrical dipole is formed by the migration of metal cations from the high-k dielectrics to SiO 2 . 10,11) These results indicate that the characterization of the chemical structure and bonding features of the high-k=SiO 2 stack is indispensable for obtaining a clear insight into the formation of electrical dipole moments.…”
Section: Introductionmentioning
confidence: 99%